Diagnosis and treatment of salivary extravasation associated with Blandin-Nuhn salivary glands: Clinical case report and literature review - Castilla-Canseco, Hernán (2024)
Mucoceles are salivary extravasation lesions associated with rupture of ducts that are generally associated with trauma. They are bluish, translucent in appearance, fluctuating on palpation, expansive and fast growing. They mostly occur in young people. The most common site of location is the mucosa of the lower lip, however, they can occur in any area that contains minor salivary glands, such as the belly of the tongue, where the Blandin-Nuhn glands are located. The frequency of lesions associated with Blandin-Nuhn’s glands is 2.25%, with approximately 400 cases reported to date. The purpose of this publication is the description of an uncommon pathology, as well as a review of the literature. The case of a three-year-old female with a history of congenital volume increase at the dorsum of the tongue without symptoms compatible with mucocele is reported, an excisional biopsy was performed under general anesthesia. The result of the histopathological study reports: extravasation mucus phenomenon. Patient evolves satisfactorily. These expansive lesions can affect the normal development of people’s lives, causing dyslalia, dysphagia and dyspnea. Treatment of this type of injuries in childhood favors adequate speech development and improves feeding conditions.